Surgical Service Utilization and In-Patient Satisfaction in Surgical Service - Joshi, Anip; Shrestha, Deepa (Journal of Nepal Health Research Council, 2024)
Background: The patient satisfaction study is an important and commonly used valid indicator for service quality improvement in healthcare institutions. The aim of this study was to assess the service utilization and patient satisfaction in patients admitted under surgical service in Bir Hospital.Methods: A prospective cross sectional analytical study was conducted in Bir Hospital, National Academy of Medical Sciences from February 2021 till June 2023. The patient satisfaction data was collected using the SAPS scale after obtaining ethical clearance from the Institutional Review Board. Data were entered and analyzed in Statistical Package for the Social Sciences version 20.0. Results: There were 152 patients included in the study categorized into conservative treatment group, elective surgery group and emergency surgery group. 32.9%(50) patients were “very satisfied”, 62.5%(95) patients were “satisfied”, 2.6%(4) were “neither satisfied nor dissatisfied” and 2%(3) were “dissatisfied” with the effect of their treatment/care. The mean satisfaction score in conservative treatment group was 22.13 ±2.53 as compared to the mean satisfaction in elective surgery group which was 21.11± 2.55 (P=0.036) and the mean satisfaction score in emergency surgery group which was 21.66 ±2.68 (P=0.64).Conclusions: The mean score and proportion of patient satisfaction regarding service utilization in patients admitted under surgical service were high with satisfaction score higher in emergency surgery group among the operative groups in Bir Hospital, National Academy of Medical Sciences.Keywords: Patient satisfaction; service utilization; surgical service.